Online information seeking behavior of Facebook's "Free Data" users in Barangay San Manuel and Barangay Citrus in San Jose Del Monte, Bulacan - Bunao, Jessie Angeli B.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
In 2015, free data was introduced when Facebook came to a partnership with Philippines mobile carrier to launch Free Basics and internet org. Both the application and the website gave Filipinos free data access to online services related to education, health, news, etc. Some Filipinos are aware of free data and its usage but in a generation where having a mobile phone is part of one’s everyday living, it is important to reach a point further than awareness. Filipinos who are part of the younger generation are most often connected through social media.

Survey and one-on-one interviews were conducted on sixty-six (66) people who have used or were currently using Free Facebook. Sixty-six (66) people were surveyed for their information seeking behavior and were interviewed for their perceptions, motivations and data-buying strategies for Free Facebook.

The survey findings show what Filipinos prioritized in their information seeking using Free Facebook. On the other hand, interview findings connect to elements of zero-rating conversations. Which top on net neutrality. Respondents’ association or unawareness of Free Basics from Free Facebook raises questions about how the service was introduced to the general public. This may lead to discussions on the effectiveness of Facebook’s Free Data initiative in the Philippines and how telecommunication companies are handling it.
Thesis
Keywords: Information-seeking behavior; Internet access; Social media -- Use -- Philippines -- Bulacan; San Jose del Monte (Bulacan, Philippines) -- Use studies